Dark anthropology, migrants and others
1 online resource
Keywords: This book offers innovative insights from across disciplines to explore the soulful survival of migrants, refugees, and displaced individuals and communities amidst stalemates, crises and compromises in human rights. Dwelling on ethnographic case studies from Asia, Africa, Latin America, the United States, and Europe, the volume illuminates the experiences of vulnerable communities, showcasing their solidarities, networks, and supportive dynamics that emerge from the harsh realities of social life. Analysing the world from the lens of fraternal relations and spaces that arise and abound in the lifeworld of the marginalised and vulnerable communities, this edited volume illustrates how without these burgeoning solidarities, migrants and other at-risk populations may have a harder struggle to navigate the socio-economic and political challenges they face. Furthermore, the book emphasises that nation-states would encounter even more profound and complex difficulties without such intricate coping mechanisms. The chapters within the volume demonstrate that these mechanisms are vital to addressing dilemmas, stalemates, and the stakeholder politics surrounding people living in precarious, hidden and dark contexts. The case studies which enrich theoretical debates also indicate how these dark contexts would be significantly more difficult to traverse without the robust and nuanced messages coded in actor solidarities and resilience.The volume is poised to attract significant attention from scholars and researchers committed to anthropology, ethnography, history, migration, international politics and refugee studies.